Ligand supplementation as a method to increase soluble heterologous protein production. - Hozjan, V; Guo, K; Wu, X; Oppermann, U (2008)
Ligand interactions are central to enzyme or receptor function, constituting a cornerstone in biochemistry and pharmacology. Here we discuss a ligand application that can be exploited to significantly increase the proportion of recombinant protein expressed in soluble form, by including ligands during the culture. Provided that a sufficiently soluble, cell-permeable and avid ligand is available, one can use it to stabilize nascently synthesized proteins, and in this manner promote solubility and prevent aggregation. To our knowledge, this concept has not been explored systematically and we provide here the first data on ligand supplementation in expression experiments across a whole human protein family: the short-chain dehydrogenases/reductases (SDR). We identified glycerrhitinic acid and its hemisuccinate ester, carbenoxolone (CBX), as ligands with variable affinities ranging from low nanomolar to micromolar binding constants against several SDRs. CBX was utilized as a culture additive in Escherichia coli expression systems against a total of approximately 500 constructs derived from 65 SDR targets, and significantly higher levels of soluble protein were obtained for more than four distinct targets. One of these, the glucocorticoid-activating enzyme type 1 11 beta-hydroxysteroid dehydrogenase (11 beta-HSD1), was solubly expressed only at a very low level (<10 microg/l culture) in the absence of ligand; however, soluble expression could be enhanced to mg/l levels by inclusion of CBX or other inhibitors. Other compounds with different chemical scaffolds were used against 11 beta-HSD1 in equivalent expression experiments yielding similar results. Taken together, if suitable ligands for a given protein are available, this approach could be tested quickly and might represent an easy and effective strategy to enhance soluble protein production, suitable for structural and functional characterization studies.